OPTICAL PROPERTIES ANALYSIS OF TiO2:Co NANOCOLUMNAR USING PHOTOLUMINESCENCE AND RAMAN SPECTROSCOPY - DHANI PRASETIYAWATI (NIM : 10213060), RAHMA
In this research, characterization and analysis of optical properties of TiO2 nanocolumnar doped by Co have been done. In the previous research, thin layer of TiO2:Co has been grown above the Si substrate (100) using metal organic chemical vapor deposition (MOCVD) with various Co-content of 0.18%; 0.33%; and 0.68%. The results of SEM and XRD consecutively show that the materials grow in columnar shape and have anatase phase with dominant orientation in (204). In this study, advanced characterization using photoluminescence and Raman spectroscopy is performed for some variation of Co-dopant concentration. This study allows us to confirm the presence of defects in the lattice of TiO2 which can indicate the presence of ferromagnetic properties at room temperature of TiO2:Co material that makes it potential as diluted magnetic semiconductors (DMS) which is useful in spintronics applications. The photoluminescence (PL) spectra show emissions from formation of Ti3+ ions, oxygen vacancies, self-trapped excitons, and shallow-trap surface state. The columnar structure of the material allows the formation of more defects in the material due to its larger surface-to-volume ratio. The intensity of PL emissions decreases with the increase of cobalt dopant concentration due to the reduced number of defects and the concentration quenching effect. The PL results confirm the cause of the increased ferromagnetic properties of TiO2:Co material as the cobalt concentration increases which generally derives from the contribution of the magnetic properties of Co atoms incorporated into TiO2 lattice and Ti3+ ions formed from the presence of oxygen vacancy in the TiO2 lattice. The Raman spectra confirm the XRD result that the materials grown are in anatase phase. On the other hand, there is a shift in wavelength for several vibrational modes which indicates the presence of oxygen vacancies and lattice expansion due to the addition of Co dopants into TiO2 system. The increase in intensity of the peak associated with the presence of polaron in the Raman spectra confirms the role of cobalt in strengthening the ferromagnetic properties of TiO2:Co.